2020
DOI: 10.1038/s41438-020-0324-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phenylpropanoid biosynthesis by MdMYB88 and MdMYB124 contributes to pathogen and drought resistance in apple

Abstract: MdMYB88 and MdMYB124 have been demonstrated to be responsible for lignin accumulation in apple under drought stress. In this study, using a metabolomic approach, we identified differentially accumulated phenylpropanoid and flavonoid metabolites in MdMYB88/124 transgenic RNAi plants under control and long-term drought stress conditions in apple roots. We confirmed the regulation of phenylalanine by MdMYB88 and MdMYB124 via UPLC-MS in apple roots under both control and drought conditions. Using Electrophoretic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…Functional analysis showed that DEGs were significantly enriched in the phenylpropanoid biosynthesis pathway. Phenylpropanoids exert a significant effect on plant responses to drought stress [ 28 30 ]. Key genes in the phenylpropanoid biosynthesis pathway have previously been shown to be modulated in drought-treated basil ( Ocimum basilicum L.) , a traditional medicinal plant [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis showed that DEGs were significantly enriched in the phenylpropanoid biosynthesis pathway. Phenylpropanoids exert a significant effect on plant responses to drought stress [ 28 30 ]. Key genes in the phenylpropanoid biosynthesis pathway have previously been shown to be modulated in drought-treated basil ( Ocimum basilicum L.) , a traditional medicinal plant [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In apple, MdMYB88 and MdMYB124 are induced by drought stress and bind to the promoters of MdVND6 and MdMYB46 , which are positive regulators of lignin deposition (Geng et al, 2018). In addition, MdMYB88 positively regulates the phenylalanine biosynthesis by binding to the promoter of the MdCM2 gene, which is required for phenylalanine biosynthesis, thereby providing more precursors for phenylpropanoid metabolism (Geng et al, 2020a). It was also reported that drought induces the expression of CmCAD1 , 2 , and 3 to enhance lignin deposition, which is critical for guaranteeing efficient axial water transport and barrier of lateral water flow in oriental melon (Liu et al, 2020).…”
Section: Regulation Of the Biosynthesis Of Phenylpropanoid Metabolitesmentioning
confidence: 99%
“…Hence, it is important to understand the function of key drought-responsive genes and investigate the physiologic mechanisms by which apple trees respond to drought [5,6] . Plants may respond to drought stress by controlling stomatal movement [7] , hormone biosynthesis [8] , the ability to scavenge reactive oxygen species [9] , accumulation of metabolic products [10] , root development [3] , transcriptional regulation [10] and microRNA biogenesis [11] .…”
Section: Introductionmentioning
confidence: 99%